Tandem acid-promoted intramolecular azide-hydrazone electrocyclization/hydrolysis approach for the synthesis of N-Aminotetrazoles. (1st January 2022) - Titenkova, Kseniia Yu; Shaferov, Alexander V.; Larin, Alexander A.; Epishina, Margarita A.; Kulikov, Alexander S.; Ananyev, Ivan V.; Fershtat, Leonid L.
Abstract: A general method for the synthesis of a series of previously unknown N -(heteroaryl)- and N -(aryl)aminotetrazoles through the tandem electrocyclization/hydrolysis of azidohydrazones was accomplished. The described protocol was suitable for a wide array of the target N -substituted aminotetrazoles which were prepared in good to high yields under smooth reaction conditions. Importantly, the presented approach is considered as a direct route to 1, 2, 5-oxadiazole-substituted aminotetrazole derivatives in good and high yields and may be realized on a gram scale. Therefore, facile synthesis of N -(heteroaryl)- and N -(aryl)aminotetrazoles unveils novel opportunities to study application prospectives of these compounds as functional materials or drug candidates. Graphical abstract: Image 1 Highlights: A general method for the synthesis of N -aminotetrazoles was developed. The reaction has a wide substrate scope and proceeds under mild conditions. No aminating reagents are required.